Cost-effectiveness of ensartinib, crizotinib, ceritinib, alectinib, brigatinib and lorlatinib in patients with anaplastic lymphoma kinase-positive non-small cell lung cancer in China - Xia Luo; Zhen Zhou; Xiaohui Zeng; Liubao Peng; Qiao Liu (Frontiers Media S.A., 2022)
ObjectiveSix anaplastic lymphoma kinase-tyrosine kinase inhibitors (ALK-TKIs), including one domestic (ensartinib) and five imported ALK-TKIs (crizotinib, ceritinib, alectinib, brigatinib, and lorlatinib), have been recommended as first-line treatments for advanced ALK-positive NSCLC in China. This study sought to examine the cost-effectiveness of these six novel therapies in Chinese patients.Material and methodsWe constructed a Markov model to compare the cost-effectiveness of the six ALK-TKIs as a first-line treatment for patients with advanced ALK-positive NSCLC from the perspective of the Chinese healthcare system. Transition probabilities were estimated by synthesizing data from the PROFILE 1,029 trial and a network meta-analysis. Health state utilities and costs were sourced from published literature, publicly available national databases, and local general hospitals. The robustness of model was assessed via deterministic sensitivity analyses and probabilistic sensitivity analyses.ResultsCompared with crizotinib, ensartinib achieved additional 0.12 quality-adjusted life-year (QALY) with marginal costs of $3,249, resulting in an incremental cost-effectiveness ratio (ICER) of $27,553/ QALY. When compared with ceritinib and brigatinib, ensartinib achieved additional 0.06 and 0.03 QALYs with substantially reduced costs. When compared with lorlatinib and alectinib, ensartinib was associated with a lower QALY and decreased total costs; the ICERs for lorlatinib and alectinib were $934,101/ QALY and $164,888/ QALY, respectively.ConclusionFor Chinese patients with advanced ALK-positive NSCLC, ensartinib was a cost-effective option compared with crizotinib, and was a dominant alternative to ceritinib and brigatinib. Although lorlatinib and alectinib were associated with prolonged survival compared with ensartinib, they were less cost-effective than ensartinib due to the overwhelming total costs.